ChemInform Abstract: Copper‐Catalyzed N‐ and O‐Arylation of Amides: Alternative Approaches to 3, 4‐Dihydroquinolin‐2‐ones, Quinolin‐2‐ones, and 12H‐Chromeno[2, 3‐b]quinolin‐12‐ones. Issue 22 (3rd June 2014) - Zhang, Xinying; Guo, Xiaojie; Fang, Liangliang; Song, Yunping; Fan, Xuesen
Abstract Copper‐catalyzed reaction of o‐bromobenzyl bromides with cyanoacetamide results in formation of 3‐cyano‐3, 4‐dihydroquinolines of type (III).